An investigation into the suitability of younger generation successors in small and medium-sized family businesses - S. P. Van Der Merwe (South African Journal of Business Management, 2011)
This study highlighted the importance of the suitability of the younger generation family members in small and medium-sized family businesses to successfully manage the business after management succession. Data from 270 questionnaires linked to 77 family businesses were collected and analysed. An Oblimin oblique rotation was performed on the principal components of the exploratory factor analysis. Five factors with eigen-values greater than one, explaining 65,78% of the variance, were extracted. These five factors describing the theoretical dimensions of the dependent variable, the suitability of the younger generation to manage the family business after succession, and the independent variables, namely value-adding by the younger generation, willingness of the younger generation, credibility of the younger generation and the degree of self-empowerment by the younger generation family members. The findings of this study indicated that the three independent variables, value-adding of the younger generation, the willingness of the younger generation to be in the family business and the credibility of the younger generation have a significant positive influence on the perceived suitability of the younger generation. Practical recommendations are suggested to ensure a smooth final transfer of the management and control of the business to the younger generation family members.
Keywords: 650